Effect of the salicylic acid and nutrition on quality of habanero pepper seedlings. - Guzmán-Antonio, Adolfo (2012)
The objective of this study was to evaluate the effect of salicylic acid and N P K fertilization on the growth and mineral status of habanero pepper seedlings (Capsicum chinense Jacq.). The study was developed in Yucatan, Mexico in November 2008 and December 2009. Seedlings were exposed to four treatments: T1) without salicylic acid and fertilization; T2) application of 10-8 M salicylic acid; T3) application of 190 mg/l de NPK and T4) application of 10-8 M of salicylic acid + 190 mg/l of NPK. The quality of seedlings was evaluated by measuring growth characteristic of shoot and root. The content of N, P, K, Ca, Mg, Cu, Fe, Zn and Mn was analyzed in whole seedlings. The slenderness and the index of quality of Dickson were also considered. The results showed significant differences (P≤0.05) on shoot growth. Applications of fertilizer caused increase on shoot dry weight. Plant height, number of leaves, stem diameter, and foliar area were not significantly different between T3 and T4. Significant differences were observed on root dry weight, specific root length, root weight density and root length density. All variables except specific root length were significantly higher with the fertilizer treatment. The latest had the highest value in the treatment T4. Significant differences (P≤0.05) were observed in tissue mineral content. Seedlings treated with T3 showed the highest content of N, P, Ca, Mg and Mn. The content of K, Zn and Fe was not significantly different between T3 and T4. In conclusion, the application of salicylic acid favored seedling growth but it did not improve significantly the quality of habanero pepper seedlings.